Satysfakcja zawodowa - zróżnicowanie odczuć ze względu na płeć pracowników - Załuska, Urszula (Job Satisfaction - Perception Differences Between Male and Female, 2008)
The analysis is based on large datasets of household data and personal characteristics gathered in ECHP database - European Community Household Panel between 1994 and 2001. The cross-national comparison of collected and acquired data gives deep insight into all important aspects of the job related satisfaction i.e. overall job satisfaction, satisfaction with type of activity, job security and with earnings in selected EU member states. The goal of the study is identification of main factors influencing the level of job satisfaction. The influence of identified factors on the job satisfaction level was analyzed in the homogenous groups of respondents classified with the use of one of demographic characteristics - gender. To achieve research goals, the logit models were used. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 6, s. 66-75